SCIENTIFIC AND RESEARCH ACTVITITIES AS THE DETERMINANT OF DEVELOPMENT OF INLAND NAVIGATION - Sosedova, Jarmila; Slesinger, Jan; Jurkovic, Martin (Doprava a spoje, 2010)
The University of Zilina through the Department of Water Transport at the Faculty of Operation and Economics of Transport and Communications prepares educated experts in the field of inland water transport. Department of Water Transport profiles theoretical and practical training for experts and is cooperating in developing and implementing international projects and grants in the field of logistics, information network and improvement of educational processes.